Um Entomophago Cryptogamico do ð˜Šð˜¢ð˜¤ð˜°ð˜¯ð˜¦ð˜®ð˜¢ ð˜³ð˜¢ð˜¥ð˜ªð˜¤ð˜ªð˜¤ð˜°ð˜ð˜¢ (Greef) Cobb (ð˜ð˜¶ð˜´ð˜¢ð˜³ð˜ªð˜¶ð˜® ð˜”ð˜¢ð˜¶ð˜³ð˜°ð˜ª n. sp.) - SaccÃ¡, Rosario Averna (REVISTA DE AGRICULTURA, 2019)
Um Entomophago Cryptogamico do ð˜Šð˜¢ð˜¤ð˜°ð˜¯ð˜¦ð˜®ð˜¢ ð˜³ð˜¢ð˜¥ð˜ªð˜¤ð˜ªð˜¤ð˜°ð˜ð˜¢ (Greef) Cobb (ð˜ð˜¶ð˜´ð˜¢ð˜³ð˜ªð˜¶ð˜® ð˜”ð˜¢ð˜¶ð˜³ð˜°ð˜ª n. sp.)